Research Progress on Performance Improvement of Spin Valve - Wu, Jianchen (Transactions on Computer Science and Intelligent Systems Research, 2025)
Spin valves, as core devices in spintronics, hold an irreplaceable position in cutting-edge fields such as information storage, magnetic sensing, and quantum computing. With increasing application demands, enhancing spin valve performance has become a common focus in both academic and industrial sectors. This paper systematically reviews recent research progress in spin valve performance enhancement, exploring key technological pathways for improving magnetoresistance ratio, enhancing temperature stability, and optimizing switching characteristics. Analyzing spin valve performance enhancement strategies from multiple dimensions: at the process level, precise control of interface quality and lattice matching significantly improves carrier transport properties; in hardware aspects, high spin polarization materials (such as Heusler alloys and Fe/MgO structures) combined with perpendicular magnetic anisotropy designs enhance device integration and thermal stability; in structural design, double-barrier structures and superlattice structures strengthen magnetoresistance response through multi-interface synergistic effects; in functional regulation, external field technologies including electric field effects, strain control, and optical field regulation provide new approaches for dynamic optimization of spin valve performance, with multi-field coupling control showing particularly significant advantages. Research indicates distinct differences in optimization strategies across application scenarios: laboratory research emphasizes combining material optimization with interface engineering, while industrial production focuses more on process simplification and cost control. Future spin valve performance enhancement will tend toward diversified development, with promising prospects for two-dimensional materials and topological materials, further deepening of multi-field coupling control technologies, and potential breakthroughs in quantum spin technology. For industrial applications, improving device reliability, consistency, and cost control remain key challenges. Cross-disciplinary integrated innovation will become the core driving force for next-generation high-performance spintronic devices, providing a solid foundation for spintronic applications in emerging fields.